AVALIAÇÃO DAS TÁBUAS ÓSSEAS VESTIBULARES E LINGUAIS DOS DENTES ANTERIORES INFERIORES E MOLARES SUPERIORES APÓS O TRATAMENTO COM OS APARELHOS FUNCIONAIS FIXOS FORSUS E TWIN FORCE BITE CORRECTOR - Bach, Cleimar Carlos (2011)
Because the consequences of the use of fixed orthopedic appliances on buccal and lingual periodontal bone are still a mystery to the orthodontist and to the clinical research, this study aimed to evaluate, using cone beam computed tomography (CBCT) changes in thickness plates of buccal and lingual bone in first molars and lower incisors and canines, after the use of fixed appliances and Twin Force (Group A) or Forsus (group B) appliances for the treatment of Class II, Division 1 malocclusion. To this end, we obtained a sample of 22 young adults, divided into two groups, according to the mandible s propulsion device. The experimental group A: 11 patients, six male and five female, mean age of 15.09 years in the Twin Force installation, and 11 patients, seven male and four female, mean age of 15.45 years in the installation of Forsus. The average time of using the Twin Force was 3.73 months and Forsus, 7.09 months. Group A had CBCT before starting the treatment (T1), before installing the Twin Force (T2), after removing the Twin Force (T3) and in group B just before the installation of Forsus (T2) and after removal it (T3). For comparison between times T2 and T3 was used paired t test, and between times T1, T2 and T3 was used analysis of variance (ANOVA) one-criterion and a Tukey s post-hoc test. For comparison between groups was used the t -test. In the inter-groups comparison between the results showed no statistically significant difference between changes in bone thickness of buccal and lingual plates; on the other hand, in the intra-group evaluation, in 48 measures evaluated, in group A, were statistically significant reductions in the buccal cervical thirds of lower anterior teeth and upper first molars, and increased cervical and middle thirds on lingual lower anterior teeth, totaling 25 significant measures. In group B, there was a significant increase in lingual bone plate on lower anterior teeth and reduction on buccal upper molars, totaling only seven significant measures, but there was more significant measures of reduction bone in buccal cervical and middle thirds in the first upper molars, in comparison with group A. There was no significant difference between the measurements obtained with voxel 0.2 mm and 0.4 mm and no sexual dimorphism. The reductions on alveolar bone thickness, especially in cervical and middle thirds buccal teeth evaluated in this study is an alert to the clinician to do this periodontal diagnostic approach before starting the orthodontic treatment.